Studi Pemanfaatan Limbah Kaca Dan Piston Bekas Sebagai Material Alternatif Kanvas Rem Sepeda Motor Dengan Menggunakan Metode Metalurgi Serbuk - Gunawan, Gilang; Nawangsari, Putri; Masnur, Dedy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Waste glass and piston can be used as alternative material to non-asbestos motorcycle brake pads based on their properties. Waste glass used as a reinforce, the piston used as a filler, and phenolic resin used as a binder. Those materials were mechanically transformed into powder with 60,100, and 60 mesh respectively. The glass, piston, and phenolic resins powder were varied into five different compositions which are A (10% glass, 50% piston, 40% phenolic resin), B (20% glass, 40% piston, 40% phenolic resin), C (30% glass, 30% piston, 40% phenolic resin), D (40% glass, 20% piston, 40% phenolic resin), E (50% glass, 10% piston, 40% phenolic resin). The powder was mixed at 45 rpm for 30 minutes, then 166 Bar initial pressure was applied in single action for 2 minutes, next it was pressed at 196 Bar in single action hot compacting at 150° for 5 minutes holding time. The green bodies were sintered at 150°C for 4 hours, finally those samples were evaluated by hardness test and wear test. The results show, the composition A has the closest hardness and wear value to commercial products, 40.549 HVN and 8.826x10-12 m3/m accordingly.Keywords: Brake Pads, Waste Glass, Waste Piston